2017
DOI: 10.1038/nature24293
|View full text |Cite
|
Sign up to set email alerts
|

IL-1R8 is a checkpoint in NK cells regulating anti-tumour and anti-viral activity

Abstract: Interleukin-1 receptor 8 (IL-1R8, also known as single immunoglobulin IL-1R-related receptor, SIGIRR, or TIR8) is a member of the IL-1 receptor (ILR) family with distinct structural and functional characteristics, acting as a negative regulator of ILR and Toll-like receptor (TLR) downstream signaling pathways and inflammation1. NK cells are innate lymphoid cells which mediate resistance against pathogens and contribute to the activation and orientation of adaptive immune responses2–4. NK cells mediate resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
196
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(204 citation statements)
references
References 42 publications
8
196
0
Order By: Relevance
“…IL‐1R8 is abundantly expressed in NK cells and it keeps under control their maturation and cytotoxic activity by inhibiting the effects of IL‐18, a cytokine of the IL‐1 family with a major role in NK cell development and function . Indeed, genetic blockade of IL‐1R8 in the mouse results in strong NK‐mediated anti‐tumor and antiviral resistance …”
Section: Regulation In the Il‐1r Familymentioning
confidence: 99%
“…IL‐1R8 is abundantly expressed in NK cells and it keeps under control their maturation and cytotoxic activity by inhibiting the effects of IL‐18, a cytokine of the IL‐1 family with a major role in NK cell development and function . Indeed, genetic blockade of IL‐1R8 in the mouse results in strong NK‐mediated anti‐tumor and antiviral resistance …”
Section: Regulation In the Il‐1r Familymentioning
confidence: 99%
“…IL‐1R8 was also shown to regulate JNK and mTOR phosphorylation in Th17 cells and NK cells, and mTOR phosphorylation driven by IL‐1 or TLR agonists derived from commensal flora in intestinal epithelial cells (Figure ). In these cell types, IL‐1R8 is therefore crucial in the modulation of metabolism, differentiation, cell cycle, and effector functions also in homeostatic conditions.…”
Section: Il‐1r8 (Tir8/sigirr)mentioning
confidence: 98%
“…Our group has recently described that murine and human NK cells express very high levels of IL‐1R8 and that IL‐1R8 is acquired during NK cell differentiation, both in terms of mRNA and protein . IL‐1R8 deficiency was associated with higher frequency and absolute number of mature NK cells in blood, spleen, bone marrow and liver, higher levels of activating NK cell receptors and increased interferon‐γ (IFNγ), granzyme B, Fas ligand expression and degranulation . Bone marrow chimeric and mixed chimeric mice experiments demonstrated that IL‐1R8 directly acts on NK cells regulating IL‐18, which is a key cytokine involved in NK cell activation .…”
Section: Il‐1r8 (Tir8/sigirr)mentioning
confidence: 99%
“…As such, there is intense interest in understanding how these functions are regulated in order to devise novel therapeutic strategies to harness NK cell function in disease. In a recent issue of Nature , a team led by Alberto Mantovani and Cecilia Garlanda have identified a new “checkpoint” or negative regulator of NK cell function known as IL‐1R8 . Their data demonstrate that IL‐1R8 expression by NK cells dampens their response to the inflammatory cytokine IL‐18, and that genetic deletion of Il1r8 unleashes NK cell dependent resistance to hepatic carcinoma, tumor metastasis and cytomegalovirus infection.…”
mentioning
confidence: 99%